Fluidmistar Media in Inquiry to Improve the Creative Thinking Skills of Senior High School Students - Susilawati Susilawati; Edi Daenuri Anwar (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Learning media an important role in supporting the learning process as a tool for students to gain mastery of the material. This study aims to produce valid fluidmistar media and analyze the increase in students' creative thinking skill after using fluidmistar learning media. Research and development is a method specifically using the ADDIE development model. The data collection technique used was a test of creative thinking skills and a student response questionnaire. The results of the expert's assessment stated that fluidmistar media was feasible to use improve creative thinking skills through inquiry learning. The implementation of fluidmistar media in inquiry learning was applied to students of senior high school in Sragen, Central Java with a total sample of 58 students. Student responses to the Fluidmistar learning media obtained good category. The results of students' positive responses indicate that the developed media to improve students' creative thinking skill and positive responses. The increase in creative thinking skill can be seen based on the pretest and posttest score tested through the N-gain test obtained at 0.74 in the high category. Fluidmistar learning media is suitable for use in inquiry learning to improve students' creative thinking skills on dynamic fluid material.Keywords: fluidmistar media; inquiry; creative thinking skillMedia pembelajaran memberikan peranan penting dalam menunjang proses pembelajaran sebagai alat bantu bagi siswa untuk mencapai penguasaan materi. Penelitian ini bertujuan untuk menghasilkan media fluidmistar yang valid dan menganalisis peningkatan kemampuan berpikir kreatif siswa setelah implementasi menggunakan media pembelajaran fluidmistar. Penelitian dan pengembangan merupakan metode yang khusus menerapkan model pengembangan ADDIE. Teknik pengumpulan data yang digunakan adalah tes keterampilan berpikir kreatif dan angket respon siswa. Hasil penilaian ahli menyatakan bahwa media fluidmistar layak digunakan untuk meningkatkan kemampuan berpikir kreatif melalui pembelajaran inkuiri. Implementasi media fluidmistar dalam pembelajaran inkuiri diterapkan pada siswa salah satu SMA Muhammasiyah 2 Gemolong Jawa Tengah dengan jumlah sampel 58 siswa. Hasil validasi ahli media diperoleh hasil rekomendasi dari aspek data dan grafik (90%), kombinasi warna (92%), pemilihan teks (88%), relevasi konten (86%), presentasi audio visual (85%) and efektivitas media pembelajaran (87%). Media Fluidmistar dinyatakan layak digunakan sebagai media pembelajaran konsep fluida. Respon siswa terhadap media pembelajaran Fluidmistar diperoleh kategori baik. Hasil respon positif siswa menunjukkan bahwa media yang dikembangkan dapat meningkatkan keterampilan berpikir kreatif siswa dan respon positif. Peningkatan keterampilan berpikir kreatif dapat dilihat berdasarkan skor pretest dan posttest yang diuji melalui uji N-gain diperoleh sebesar0,74 dengan kategori tinggi. Media pembelajaran fluidmistar cocok digunakan dalam pembelajaran inkuiri untuk meningkatkan kemampuan berpikir kreatif siswa pada materi fluida dinamis.